Applications of Internet of Things for smart farming – A survey. (2021) - Balasubramaniyan, M.; Navaneethan, C.
Abstract: In today's world agriculture is very important in farmer and people's life, because without food production people cannot able to live. Farmer's day-by-day make food production in the world. This food production process has many difficulties in farmer's normal life in current world. The farmer's facing the difficulties in manually are monitoring the water, monitoring the human works, monitoring the animals, monitoring the dangerous animals, cost, and etc. These difficulties will be overcome through IoT technologies. This technology used to monitor the water through sensor, monitoring the normal animals and dangerous animals through sensor because farmer's avoid risk and disease, and finally save and improve the farmer's production time, production cost, and health. The researchers are searching technological key to improve the agriculture existing services by setting technology of IoT. In this paper, based on the survey paper, to help the farmers for increase the crop production between high and low quality through various algorithms. This algorithm used to find the best quality, and used to implement the manage climate change, soil erosion, and availability of water efficiently in various sensors. Finally, discuss about the trends and platform of the agriculture with various applications and finding the research gap.